SISTEM INFORMASI PENJUALAN HIPA ( HIMPUNAN PELUKIS AMBARAWA ) DI AMBARAWA SEMARANG BERBASIS WEB DENGAN E-COMMERCE (Information Technology and Telematics, 2013)
Sales Information Systems at HIPA engaged in painting a painting owned by a variety of characters. HIPA often exhibited paintings ever held, so that the paintings were owned by HIPA less widely known by the public. But HIPA has shortcomings or difficulties in selling their - their work, while the work of HIPA be sold only at the exhibition - exhibition of paintings. Here the author has the initiative to assist in the sale of their work with the help of HIPA internet media, namely the method E - COMMERCE (sales by internet media or on-line). With the web sales on-line by the method of E - Commerce, can help HIPA in selling their work to the whole world. In other words, the existence of such a program, as well as expanding the sales area by HIPA (Ambarawa Painters Association).Keywords: Sales Information System, E - Commerce.